Evaluación de políticas públicas del plan nacional del buen vivir dirigidas a las organizaciones agroproductivas solidarias de la zona 4 - Alcívar Bravo, Gema Estefanía (2019)
The present investigation consisted of evaluating the public policies of the Good Living National Plan 2013-2017, to show the fulfillment of the objectives set by the government; For this, 4 phases were developed, the first one included identifying the public policies aimed at the solidarity agro-productive organizations of the zone, proceeding with a broad search in the National Plan of Good Living, choosing 48 public policies developed in the next phase The second phase was to obtain the perception of the level of application of public policies by those responsible for the control and execution of public policies, that is, checking a degree of compliance in the associates and non-associates of the solidarity organizations, conducting a survey in the province of the zone and using the SPSS software that allowed to make tables where the results are specified to obtain an understandable and efficient analysis, continuing with the third phase that was to perform a contrast of the level of application of public policies for the benefit of the Agroproductive Organizations of the zone, where ther The results of phase 2 were contrasted with the survey of associates and non-associates of 19 cantons of the province of Manabí, where they cataloged the public policies linked to these organizations or cooperatives as unfulfilled, and in this way determined that under the perspective of those responsible for compliance with public policies in Ecuador, referents are represented at a medium level and for non-members at a high level.